JAPANESE WOMEN’S ACTIVISM SUSTAINS A LIFE-GIVING COMMUNITY IN THE PANDEMIC - Peracullo, J. (Acta Theologica, 2023)
The COVID-19 pandemic brought significant challenges to the women dependent on the healthcare and tourism industries for the livelihood of their families. These challenges opened opportunities for organisations to alter their traditional forms of assistance into modalities that address the effects of the pandemic. I explore the Asian Women Empowerment Project (AWEP), a Japanbased organisation dedicated to helping poor women in Asian countries attain economic power. During the pandemic, AWEP attuned its programmes to respond to its challenges. Using ecofeminist theologian Sallie McFague’s ecological model, I demonstrate that AWEP reveals Japanese women’s acute understanding of a need for an ecological ethics of solidarity that includes ecological interests, a consciousness of solidarity, and cooperation through global sisterhood, which posits that women the world over share everyday experiences regardless of race, nationality, ethnicity, class, or economic status and, therefore, should help one another.